Analisis Kebutuhan Angkutan Umum Penumpang Trayek Pontianak Rasau Jaya - Nernawani Nernawani; Indah Rosanti; Etty Rabihati (Politeknik Negeri Pontianak, 2018)
Public transportation is a familiar mode of land transportation for road users, now public transportation becomes the rarest thing in Pontianak area, especially Pontianak - Rasau Jaya route, for it is considered necessary to know what variables are very influential on the performance of public transportation. The purpose of this study is to know what variables are very influential performance of public transport, how much Load Factor and how many public transports should be provided to serve from the Road Trajectory Pontianak - Rasau Jaya. From the results of this study found that variables that are very influential on the performance of public transport Tayek Pontianak-Rasau Jaya is the Length of Tayek, Reability, and Comfort, security and safety. While LF during peak hours 5.11 while the hour is not busy at 1.79, while the estimated number of buses 2 pieces.